Analysing the institution of caliphate in the context of political Islamists - Dogan, Recep (Penerbit Universiti Kebangsaan Malaysia, 2019)
The Caliphate is an important concept for Muslims, especially for those who have been experiencing turmoil, disorder and conflict in their lands, as it presents as a collective body that is to be governed with fairness, assuring safety and justice for all associated with it. Once again it has resurfaced as a hot topic, debated by Muslims and non-Muslims alike. The advent of the 21st century has seen the establishment of many varied initiatives, all in attempt to re-establish the concept of a caliphate, however many of these have been short-lived and have received little support. Gradually, with the declining influence of terrorist organisations, the debate has almost lost its significance. This was until more recently, when the political Islamists of Turkey reignited the discussion through their claims of leader Recep Tayyip Erdogan as the rightful caliph of Muslims, inviting all Muslims to give him their pledge of allegiance. Therefore, it becomes imperative to examine the institution of the caliphate, its relevance to Muslims through identifying the nature of the caliphate and its theological and political values. More importantly, this paper aims to analyse the negative effects of the Justice and Development Party (the AKP) on Muslims, in Turkey and in other parts of the world, as a result of the party’s methods of conveying its extreme views through Islamic concepts and extremist religious interpretations. Political Islamists use primary Islamic sources and religious arguments to justify the declaration of caliphate.